The Impact of Integrin β2 on Granulocyte/Macrophage Progenitor Proliferation. (7th February 2019) - Zhang, Li-Jie; Yan, Cen; Schouteden, Sarah; Ma, Xiao-Juan; Zhao, Dong; Peters, Thorsten; Verfaillie, Catherine M.; Feng, Ying-Mei
Abstract : Previously, we reported that although the HSPC frequency in bone marrow cells (BMC) was comparable between β2−/− and β2+/+ mice, transplantation of β2−/− BMC into lethally irradiated CD45.1 recipient resulted in more myeloid cell production than β2+/+ BMC. The objective of this study is to address if integrin β2 deficiency skews granulocyte/macrophage progenitor (GMP) proliferation. FACS analysis demonstrated that GMP frequency and cell number were higher and megakaryocyte/erythrocyte progenitor frequency and cell number were lower in β2−/− mice than β2+/+ mice. However, the common myeloid progenitors (CMP) frequency and cell number were similar between the two groups. The increased GMP number was due to GMP proliferation as evidenced by the percentage of BrdU-incorporating GMP. Whole genome transcriptome analysis identified increased FcεRIα expression in β2−/− CMP compared to β2+/+ CMP. FcεRIα expression on β2−/− GMP was detected increased in β2−/− mice by qRT-PCR and FACS. Although transplantation of FcεRIα hi GMP or FcεRIα lo GMP into lethally irradiated CD45.1 recipient resulted in comparable myeloid cell production, transplantation of β2 deficient FcεRIα hi GMP generated more myeloid cells than β2+/+ FcεRIα hi GMP. GATA2 expression was increased in β2−/− GMP. Using a luciferase reporter assay, we demonstrated that mutation of the GATA2 binding site in the FcεRIα promoter region diminished FcεRIα transcription. In vitro, the addition of IgE, the ligand of FcεRIα, promoted GMP expansion, which was abrogated by inhibition of JNK phosphorylation. Integrin β2 deficiency promoted GMP proliferation and myeloid cell production, which was mediated via FcεRIα/IgE-induced JNK phosphorylation in GMP. Stem Cells   2019;37:430–440 : Abstract : Integrin β2 governs granulocyte/macrophage progenitor (GMP) proliferation under control. β2 deficiency upregulates GATA2/FcεRIα expression in GMP. Binding of IgE to FcεRIα stimulates GMP proliferation which is abrogated by the inhibition of JNK phosphorylation. Ultimately, GMP become constitutively activated for proliferation, leading to myelocytosis.